PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rapa L.) DENGAN KONSENTRASI DAN INTERVAL WAKTU PEMBERIAN PUPUK ORGANIK CAIR KOTORAN AYAM - Alvera Prihatini Dewi Nazari; Susylowati Susylowati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
Pak choy is a vegetable that content high nutrition, beneficial for health, and the price is higher compared to other types of mustard greens, so that pak choy cultivation has bright prospects. One effort to get quality pak choy is by providing chicken manure liquid organic fertilizer (LOF). The research was conducted to study: the interaction; concentration of LOF; and time interval for applying LOF that provides the best growth and yield of pak choy. The experiment was conducted from June to August 2021 in Sumber Sari Village, Sebulu District, Kutai Kartanegara Regency, East Kalimantan Province. The experiment was arranged in a Split Plot Design with six replications. The concentration of LOF as the Main Plot, consisting of four levels, namely control (0), 25, 50, 75 mL L-1; and time interval for applying LOF as Subplots, consisted of every 2 and 4 days. Data were analyzed using analysis of variance, continued with Duncan's Multiple Range Test at 5% level. The relationship between plant dry weight and LOF concentration was determined using polynomial orthogonal regression and correlation analysis. The results showed that the interaction and the time interval for applying LOF was not significantly different on all variables; while the efffect of LOF concentration is significantly different on all variables. A concentration of 25 mL POC L-1 is able to meet the nutritional needs of pak choy. The shape and strength of the relationship between dry weight of pak choy and POC concentration is linear and very strong with the regression equation ŷ = 3.263 + 0.0615x; correlation coefficient (r) 0.8344; and the coefficient of determination (R2) is 0.6963.